Anti-Inflammatory Drugs and Immunosuppressants in Rheumatological and Musculoskeletal Diseases - Mustafa, Syed Hassan; Durrani, Talha; Adnan, Saqib; Khan, Rabnawaz (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine drug compliance among patients with rheumatological and musculoskeletal diseases and to identify the reasons behind poor compliance. Study Design: Cross-sectional study. Place and Duration of Study: Department of Rheumatology Lady Reading Hospital, Peshawar Pakistan, from Aug 2020 to Feb 2021. Methodology: All patients aged 16 to 70, of either gender with inflammatory rheumatic diseases who were prescribed conventional DMARDs for at least six months were included in the study. Results: Two hundred and eighteen patients were included in the study. There were 59(27.1%) males and 159(72.9%) females with a mean age of 38.56±4.75years. There were 156 SPRA patients (71.5%), while SLE and SNIA accounted for 22(10.1%) and 17(7.8%) cases, respectively. Methotrexate was the most commonly prescribed medicine, 158(72.5%) while 90(41.3%) patients were prescribed Hydroxychloroquine and 43(19.7%) patients were prescribed Sulfasalazine. Regarding compliance, 112 (51.4%) patients were found to have good drug adherence. On the other hand, side effects and lack of awareness were found to be the most common cause of poor medication adherence. Conclusion: We concluded that adherence to medication among patients with inflammatory rheumatic and musculoskeletal diseases is poor